Noodzakelijkheid bij William Whewell: De ontwikkeling Van een concept - Ducheyne, Steffen (Tijdschrift voor Filosofie, 2007)
The immense oeuvre of William Whewell (1794-1886), a Victorian monument by itself, has to some extent been treated in a stepmotherly fashion by philosophers and historiansof philosophy. This paper attempts to conceptually clarify Whewell's notion of necessity, which was a core notion in his philosophical project. The author also sketches in broad lines the historical development of this notion in Whewell's thinking and points tothe intertwinement between Whewell's philosophy and theology. Whewell's philosophical work was deeply based on the history of science and his doctrine of Fundamental Ideas can be interpreted as an attempt to historicize Kant's transcendental categories.